Clonal Architecture of Secondary Acute Myeloid Leukemia - Walter, Matthew J; Shen, Dong; Ding, Li; Shao, Jin; Koboldt, Daniel C; Chen, Ken; Larson, David E; McLellan, Michael D; Dooling, David; Abbott, Rachel; Fulton, Robert; Magrini, Vincent; et al. (The New England journal of medicine, 2012)
Whole-genome sequencing of samples from seven subjects with secondary acute myeloid leukemia identified somatic mutations. These data, together with genotype analysis of the antecedent myelodysplastic syndromes (MDS), revealed the clonal evolution of MDS and secondary AML. The myelodysplastic syndromes, a heterogeneous group of diseases characterized by ineffective hematopoiesis, are the most common cause of acquired bone marrow failure in adults. 1 Secondary acute myeloid leukemia (AML) develops in approximately one third of persons with myelodysplastic syndromes. 2 Clinical discrimination between the myelodysplastic syndromes and secondary AML currently rests predominantly on cytomorphologic analysis, since patients with myelodysplastic syndromes have dysplastic hematopoiesis and a myeloblast count of less than 20%, whereas those with a myeloblast count of 20% or more have AML. Although considerable overlap exists between the spectrum of cytogenetic and molecular lesions seen in the two disorders, there . . .